A Case of Tracheobronchial Amyloidosis Treated with Endobronchial Therapy - Cetinkaya, Erdogan; Ozgul, Mehmet Akif; Kirkil, Gamze; Ozgul, Guler; Acat, Murat; Kamiloglu, Emine; Onaran, Hilal (Bilimsel Tip Publishing House, 2013)
Primary isolated tracheobronchial amyloidosis is an uncommon disease. It manifests in symptoms such as progressive dyspnea, cough, and haemoptysis. Airway obstruction can cause atelectasis and recurrent bronchopulmonary infections. A 47-year old man was admitted with the complaint of dyspnea upon exertion of 15 years duration. It is learned that he had a productive cough in winter, and received treatment for bronchial asthma, but had no recovery. Hemoptysis added to his complaints for 10 days, and he had a smoking history of 30 packet/year. Upon physical examination, he had prolonged expirium, and other system signs were normal. Laboratory findings; WBC: 7.100, Hb: 14, Hct: 42.6%, Plt: 479.000, ESR: 80 mm/sec, biochemical parameters were within the normal range. The posteroanterior radiogram of the chest revealed bilateral hilar fullness, and double contour on the right diaphragm. Results of pulmonary function tests were as follows; FEV 1 /FVC: 44%, FEV 1 : 47%, FVC: 84%. A computed tomography scan of the chest showed clear emphysemal areas in lung parenchyma, and diffuse thickening on the wall of the trachea, bilateral main bronchii, and segmental bronchii. Fiberoptic bronchoscopy revealed multiple endobronchial lesions on the walls of trachea, and subsegmental bronchii, and mucosal infiltration. A biopsy from these lesions revealed pink-purple amyloid accumulation on mucosal connective tissue, mucosal gland wall, and mucosal vascules after painting with crystal violet and Kongo red. The patient was diagnosed as tracheobronchial amyloidosis, and argon plasma coagulation applied under general anesthesia first to the left main bronchus, and then the right main bronchus and trachea during 2 sessions. After coagulation, mechanical resection was applied. Cryotherapy was applied to the remaining tissue. After treatment, his symptoms were significantly improved. Although spontaneous resolution has been reported in the tracheobronchial amyloidosis, most cases require multiple therapeutic interventions in order to control progressive respiratory symptoms.
Endobronşiyal tedavi uygulanan trakeobronşiyal amiloidoz olgusu
Keywords: Tracheobronchial amyloidosis; mechanical resection; cryotherapy